2020
DOI: 10.37934/araset.20.1.2741
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review of Particle Dispersion of Cavity Flow

Abstract: Particles dispersion studies have attracted researchers' interest in understanding the physics behind the phenomena. Fluid-particle transport related to cavity flow is relevant to several natural and engineering applications such as cleaning of process equipment. This paper intends to provide a brief review of researches on the impact parameters, including geometrical parameters of the cavities, flow-related parameters, heat transfer and fluid-particles interaction and identifies opportunities for future resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
2
5
0
Order By: Relevance
“…The flow pattern is usually at the exit of the nozzle, but due to the rib with a 3:3 aspect ratio, this pattern is seen at the rib exit. The influence of rib's geometry on the changes of flow characteristics are consistent with the observation obtained in Sahak et al, [18] who observed the variation of flow regime with the cavity geometry.…”
Section: Resultssupporting
confidence: 91%
“…The flow pattern is usually at the exit of the nozzle, but due to the rib with a 3:3 aspect ratio, this pattern is seen at the rib exit. The influence of rib's geometry on the changes of flow characteristics are consistent with the observation obtained in Sahak et al, [18] who observed the variation of flow regime with the cavity geometry.…”
Section: Resultssupporting
confidence: 91%
“…While for v-velocity plots (right), the negative v-velocity zone becomes thinner and longer. These phenomena are consistent with the experimental results and can be explained by a higher mass transfer rate of the fluid inside the cavity as Re increases (Sahak et al, 2020). From all these findings, the flow topology is proved to be highly dependent upon the Reynolds number.…”
Section: Reynolds Number Effectssupporting
confidence: 90%
“…Experimental investigations on LDC flow are always undergoing a parallel development with CFD, from the 1980s until recently (Sahak et al, 2020). Although with a certain geometrical simplicity, the flow physics inside this LDC is not such simple.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the other main general approaches to the second law can be seen in references [33][34][35]. However, there are some challenges to the second law [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%